Navigating Risks in the Emergency Room: A Comprehensive Review of Patient-Related Violence Against Medical Workers in Emergency Departments - Alyami, Mahdi Salem Hussein; Alyami, Mohammed Salem Hussain; Alyami , Mahfouz Masoud Bin Mana; Osman, Mohammed Jaffer Ahmed; AL yami, Ghanem Mahdi Mohammed; Alyami, Abdullatif Ali Ali; Alrajab, Saif Ali Ali; Balhareth, Yasser Abdullah Mubarak; Alyami , Mana Mohammed Mana; Al-Abbas, Muhammad saleh Hamad (Journal of Ecohumanism, 2024)
Patient-related violence against healthcare workers in emergency departments (EDs) has become a growing concern worldwide, impacting the safety and well-being of medical staff, the quality of patient care, and the overall healthcare system. This review provides a comprehensive analysis of the prevalence, types, and contributing factors of patient-related violence in ED settings, including environmental stressors, patient conditions, organizational policies, and social influences. The physical and psychological impact on ED workers, such as injury, stress, burnout, and job dissatisfaction, is also explored. Furthermore, current prevention and management strategies are reviewed, including security measures, training programs, policy frameworks, and support systems. The article identifies challenges, including underreporting and research gaps, and offers recommendations for improved reporting systems, policy reforms, and targeted training to equip ED staff to handle aggressive behavior. By highlighting these key insights, this review underscores the urgent need for evidence-based interventions to protect healthcare workers in EDs and improve workplace safety and patient care outcomes.